(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Volkova Ya. Keywords: destructive communication, destructiveness, conceptual space, conceptualization of emotions, emotion concept, conceptual metaphor. The article presents the results of the analysis of the conceptual-image component of the emotional concept of «JEALOUSY» in Russian linguistic culture. Some conclusions are made concerning the shift of the basic characteristics of the concept «JEALOUSY» in the Russian language consciousness. The author considers basic conceptual metaphors as well as some linguistic means of the concept verbalization. It is concluded that there is a common conceptual framework of emotions within the core of the conceptual space of destructiveness.